Cannabinoid Hyperemesis Syndrome: A Case Study in a Tunisian Young Man - Haythem Yacoub; Hajer Hassine; Héla Kchir; Nadia Maamouri (Case Reports in Medicine)
The increasing prevalence of cannabis use in the world requires awareness of cannabis-related disorders such as cannabinoid hyperemesis syndrome. This syndrome includes cyclic episodes of nausea, vomiting, and the learned behavior of hot bathing in individuals with chronic cannabis use. We present the case of a suspected cannabinoid hyperemesis syndrome that required a review of the literature to retain the diagnosis. The following case illustrates how cannabinoid hyperemesis syndrome awareness may lead to the diagnosis.